Clinical and Salivary Findings in Patients with Different Types of Orthodontic Brackets - Antonija Jurela; Karlo Sudarević; Ana Budimir; Vlaho Brailo; Božana Lončar Brzak; Bernard Janković (Acta Stomatologica Croatica, 2019)
Aim: Data regarding different types of orthodontic brackets and ligation and various clinical and salivary findings are scarce. Therefore, the aim of this study was to compare clinical and salivary findings in patients with different types of fixed orthodontic appliances. Subjects and methods: Decayed, missing and filled teeth index (DMFT) and plaque index, salivary flow rate, salivary pH and prevalence of white spot lesions were determined in 83 patients with different types of orthodontic brackets and ligation (metal passive self-ligating brackets, conventional metal brackets, mono-crystal brackets and polycrystalline active self-ligating brackets), before and six months after the beginning of fixed orthodontic treatment. The patients were recruited in a private dental office, in the period of two years. The group comprised 83 patients (mean age: 15.14 ± 1.66 years), including 52 women (mean age: 15.08 ± 1.68) and 31 men (15.24 ± 1.64). Statistical analysis was performed by use of dependent and independent samples t-test as well as one way ANOVA, Wilcoxon signed rank test and the Kruskal Wallis test. P-values below 0.05 (p<0.05) were considered significant. Results: DMFT and salivary flow have shown a significant increase, while salivary pH has shown a significant decrease in the observed time interval, in all patients irrespective of type of brackets and ligation. Among patients with different bracket material, no significant differences were found in any of the observed parameters. Conclusion: Although salivary flow rate is increased in patients with fixed orthodontic appliances which can have caries-protective effect, DMFT also increases and salivary pH decreases six months after the beginning of the treatment independently of bracket material or ligation type. All patients should receive instructions for precise oral hygiene and dietary habits before the beginning of fixed orthodontic therapy and at every dental check-up.